Chrysanthemum indicum L. Extract Induces Apoptosis through Suppression of Constitutive STAT3 Activation in Human Prostate Cancer DU145 Cells. (22nd March 2012) - Kim, Chulwon; Kim, Moo‐Chang; Kim, Sung‐Moo; Nam, Dongwoo; Choi, Seung‐Hoon; Kim, Sung‐Hoon; Ahn, Kyoo Seok; Lee, Eun Ha; Jung, Sang Hoon; Ahn, Kwang Seok
<x xml:space="preserve">Abstract</x> Chrysanthemum in dicum L. has been shown to possess antiinflammatory and anticancer activities, but its molecular targets/pathways are not yet fully understood in tumor cells. In the present study, the potential effects of C. indicum on signal transducer and activator of transcription 3 (STAT3) signaling pathway in different tumor cells were examined. The solvent fractions (hexane, CH2Cl2, EtOAc, and BuOH, ) were obtained from a crude extract (80% EOH extract) of C. indicum. The methylene chloride fraction of C. indicum (MCI) exhibited strong cytotoxic activity as compared with the other fractions and clearly suppressed constitutive STAT3 activation against both DU145 and U266 cells, but not MDA‐MB‐231 cells. The suppression of constitutive STAT3 activation by MCI is associated with blocking upstream JAK1 and JAK2, but not Src. MCI downregulated the expression of STAT3‐regulated gene products; this is correlated with the accumulation of the cell cycle at sub‐G1 phase, the induction of caspase‐3 activation, and apoptosis. Moreover, the major components of the MCI were bioactive compounds such as sudachitin, hesperetin, chrysoeriol, and acacetin. Sudachitin, chrysoeriol, and acacetin also exerted significantly cytotoxicity, clearly suppressed constitutive STAT3 activation, and induced apoptosis, although hesperetin did not show any significant effect in DU145 cells. Overall, our results demonstrate that MCI could induce apoptosis through inhibition of the JAK1/2 and STAT3 signaling pathways. Copyright © 2012 John Wiley & Sons, Ltd.